Qualitative analysis to create scenarios regarding the relationship between Las Bambas mining company and local populations - Vargas Mayer, Luis Enrique (2024)
This research work is focused on problems of social interaction between a large-scale mining company, “Las Bambas” and its surrounding populations; Specifically, it focuses on looking for future scenarios of this social interaction that serve as an exploratory basis for future research. To this end, this work focuses on the qualitative analysis of journalistic media of various political tendencies and seeks to project future scenarios based on three variables: effects of social responsibility, social conflict and the trinomial “economy – power – inefficiency of the apparatus state"; These variables are understood to be of great importance for social transformation and are analyzed from the theoretical basis to integrating it with reality based on content analysis.  The result allows us to deliver 4 scenarios: trend, utopian, normative and contrast; finding that, in a trend scenario, which is projected from the current context and without finding important adjustments to the current reality, results in a scenario where populations persist in achieving shareholding, economic dependence, situations of social conflict and increase of radical ideas.